2013
DOI: 10.1007/s40258-013-0021-5
|View full text |Cite
|
Sign up to set email alerts
|

A UK-Based Cost-Utility Analysis of Indacaterol, A Once-Daily Maintenance Bronchodilator for Patients with COPD, Using Real World Evidence on Resource Use

Abstract: IntroductionChronic Obstructive Pulmonary Disease (COPD) is a chronic, progressive disease that is not curable. However, there are effective treatments available. In the UK, long-acting bronchodilators are first-line treatments for COPD patients requiring maintenance therapy, and there are several options available. The aim of this study is to establish, from the UK National Health Service (NHS) perspective, the cost-effectiveness profile of indacaterol, the first once-daily long-acting beta2-agonist (LABA), c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 19 publications
0
26
0
2
Order By: Relevance
“…Although, as already mentioned,indacaterol is cost-effective compared to tiotropium and salmeterol [33] and notwithstanding what we have previously illustrated on the potential positioning of ultra-LABAs in the treatment of COPD, no guideline indicates ultraLABAs as first choice drugs compared to LAMAs. In effect, there is not published evidence that ultraLABAs are definitely more effective than LAMAs as monotherapy.…”
Section: Expert Commentarymentioning
confidence: 79%
See 2 more Smart Citations
“…Although, as already mentioned,indacaterol is cost-effective compared to tiotropium and salmeterol [33] and notwithstanding what we have previously illustrated on the potential positioning of ultra-LABAs in the treatment of COPD, no guideline indicates ultraLABAs as first choice drugs compared to LAMAs. In effect, there is not published evidence that ultraLABAs are definitely more effective than LAMAs as monotherapy.…”
Section: Expert Commentarymentioning
confidence: 79%
“…In a pooled analysis of data from three randomized, double blind, placebo-controlled studies, both indacaterol doses, 150 and 300 μg, were associated with significant reductions in exacerbations versus placebo [29]. However, the Indacaterol: providing opportunity to re-engage patients with life (INVIGORATE) study showed that tiotropium offered greater protection from exacerbations than indacaterol [30], but the absolute number of events was small and the difference between treatments was of uncertain clinical importance.A post hoc analysis has shown that blood eosinophil count ≥2%, which is a promising biomarker of response to ICSs in patients with COPD [31], does not appear to predict bronchodilator response to β 2 -agonists in either ICS users or non-users [32].It is remarkable to point out that a UK-based cost-utility analysis of indacateroldemonstrated that indacaterol can produce better outcomes at a lower cost to the healthcare system compared with both tiotropium and salmeterol and is likely to remain cost-effective under a range of assumptions [33]. In particular, the proportion of patients in each of the COPD stages and the mortality rate associated with very severe COPD are the variables with the largest impact on the results.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Необходимо отметить, что проведенный в Ве-ликобритании анализ рентабельности применения индакатерола показал, что индакатерол обеспечи-вал лучшие результаты при меньшей стоимости по сравнению с тиотропием и сальметеролом и, скорее всего, остается экономически эффективным по ряду положений [33]. В частности, доля больных с каждой из стадий ХОБЛ и уровень смертности, связанной с крайне тяжелой ХОБЛ, являются наиболее значимы-ми параметрами, влияющими на результат лечения.…”
Section: обзорыunclassified
“…The British study 8 compared indacaterol (the sponsored drug) with tiotropium and salmeterol in patients with chronic obstructive pulmonary disease. Efficacy and utility were derived from multi-centre international randomised controlled trials on indacaterol, chronic obstructive pulmonary disease-related mortality rates from a Spanish economic evaluation.…”
Section: Variablesmentioning
confidence: 99%